Preparation method and application of Mxene composite bimetallic material
By growing bimetallic active sites in situ on Mxene material, Mxene composite bimetallic material was prepared, which solved the problem of low catalytic activity and stability of existing metal catalysts, and significantly improved the performance of lithium-sulfur batteries.
Patent Information
- Application Number
- CN202311363219.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the catalytic activity and stability of metal catalysts used in lithium sulfur batteries are low, resulting in poor performance of lithium sulfur batteries and cannot meet the demand.
Using the preparation method of Mxene composite bimetallic material, the bimetallic active sites are grown in situ on the modified Mxene material to form a multi-layer pore structure and a large active area Mxene composite bimetallic material.
This material exhibits excellent catalytic activity and stability in the lithium-sulfur battery separator material, improves the rate performance, cycle stability and specific capacity of the lithium-sulfur battery, and inhibits the shuttle effect and loss of active substances.
Smart Images

Figure CN119857531A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of composite materials, and in particular relates to a preparation method and application of a Mxene composite bimetallic material. Background Art
[0002] Rechargeable lithium-sulfur batteries (Li-S) are environmentally friendly, low-cost and have high specific capacity (1675 mAh g -1 ) is therefore considered a candidate to replace traditional lithium-ion batteries. However, since lithium-sulfur batteries generate some soluble lithium polysulfide (LiPS) intermediates (Li2S x ,3≤x≤8), insulating sulfur (S8) and lithium sulfide (Li2S). These soluble intermediates can cause a "shuttle effect", resulting in a serious loss of active sulfur and corrosion of the lithium metal anode. In addition, the slow sulfur conversion reaction leads to the accumulation of LiPS in the cathode, which further exacerbates the shuttle effect. As a result, lithium-sulfur batteries have problems such as poor rate performance, short cycle life, and low Coulomb efficiency (CE). At present, in order to accelerate the sulfur species conversion reaction and reduce the shuttling behavior of polysulfides, the commonly used method is to add metal electrocatalysts to lithium-sulfur batteries. However, the metal catalysts conventionally used in the prior art do not have a stable surface structure, nor do they contain multi-scale porous channels that can withstand long-term cycles, resulting in low catalytic activity of the metal catalysts; at the same time, some metal-type catalysts are prone to aggregation and structural collapse during the charge and discharge process, which makes the catalytic stability of the metal catalysts low, ultimately resulting in unsatisfactory performance of lithium-sulfur batteries and unable to meet people's needs. Summary of the invention
[0003] In order to solve the technical problems that the catalytic activity and catalytic stability of metal catalysts used in lithium-sulfur batteries in the prior art are both low, the present application proposes a method for preparing a Mxene composite bimetallic material. The Mxene composite bimetallic material obtained by the preparation method has excellent catalytic activity and catalytic stability when used for preparing lithium-sulfur battery diaphragm materials.
[0004] In order to achieve the above-mentioned purpose, this application adopts the following technical solutions:
[0005] A method for preparing a MXene composite bimetallic material comprises the following steps:
[0006] (1) Preparation of Mxene materials
[0007] Mix Ti3AlC2 powder with ethanol and grind it in a ball mill to obtain a uniform slurry; dry the slurry to obtain dry powder; heat the dry powder, HF and deionized water in a pressure bottle to 150-200°C and keep it for 4-10 hours, then cool it naturally to room temperature; then wash it with N,N-dimethylformamide to obtain Mxene material;
[0008] (2) Modification of Mxene materials
[0009] The Mxene material obtained in step (1) is placed in a tetraethylammonium hydroxide solution, stirred for 3-5 hours, and then centrifuged to obtain a modified Mxene material;
[0010] (3) Preparation of Mxene composite bimetallic materials
[0011] Dissolving terephthalic acid in a mixed solution of N,N-dimethylformamide and acetonitrile to obtain a base solution;
[0012] Dissolving the modified Mxene material obtained in step (2) in a mixed solution of N,N-dimethylformamide and acetonitrile and stirring evenly to obtain a middle layer liquid;
[0013] Dissolving the metal salt ligand powder in a mixed solution of N,N-dimethylformamide and acetonitrile to obtain an upper layer liquid;
[0014] The bottom liquid, the middle liquid and the upper liquid are sequentially poured into the reaction bottle and the bottom liquid, the middle liquid and the upper liquid are always kept sequentially stacked and in a layered state, and then the reaction bottle is placed at 15-25° C. for 10-24 hours to react to obtain a reactant;
[0015] The reactants are alternately centrifuged and washed 2-5 times with N,N-dimethylformamide and chloroform and then dried to obtain the Mxene composite bimetallic material.
[0016] Furthermore, in the step (1), the mixing ratio of the Ti3AlC2 powder and the ethanol is 1 g: (4-6) ml.
[0017] Furthermore, in the step (1), the rotation speed of the ball mill is 600 rpm, and the grinding time is 3-5 h.
[0018] Furthermore, the slurry is dried in step (1) in a vacuum oven at 50-70° C. for 10-14 hours.
[0019] Furthermore, in the step (1), the addition ratio of the dry powder, HF and deionized water is (150-200) mg: 3 ml: 60 ml.
[0020] Furthermore, the concentration of the tetraethylammonium hydroxide solution in step (2) is (30-35) wt%.
[0021] Furthermore, the addition ratio of terephthalic acid in the base liquid to the modified Mxene material in the middle layer liquid is 2:1.
[0022] Furthermore, the metal salt ligand powder in step (3) includes powder A and powder B, wherein powder A is any one of Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O, Zn(CH3COO)2·2H2O, Fe(CH3COO)3·4H2O, and Cu(CH3COO)2·H2O, and powder B is Mn(CH3COO)2·4H2O.
[0023] Furthermore, the molar ratio of the powder A to the powder B is (1-4):1.
[0024] The beneficial effects of this application are:
[0025] 1. MXene is an emerging two-dimensional metal carbide with excellent conductivity, rich polar functional groups and excellent mechanical flexibility. This application uses modified MXene materials as conductive supports and in-situ grows bimetallic active sites on MXene materials, so that MXene composite bimetallic materials have multi-layer pore structures and large active areas. When used, it can not only achieve rapid transfer of electrons and ions, but also prevent metal aggregation in LiPS conversion reactions. At the same time, metal organic framework materials act as spacers to isolate multi-layer MXene materials and evenly distribute them between layers, thereby retaining the active area required for polysulfide electrocatalysis. More importantly, the introduction of metal organic frameworks effectively accelerates the redox reaction of polysulfides and improves the utilization rate of sulfur.
[0026] Specifically, the Mxene composite bimetallic material can make Li + Rapid diffusion reduces the energy barrier for Li2S precipitation and dissolution, thereby enhancing the LiPS conversion kinetics; at the same time, it can also expose the active center of the bimetallic, providing excellent synergistic effects for the catalytic reaction. That is, the Mxene composite bimetallic material has both the adsorption effect on lithium polysulfide and the catalytic effect of catalyzing its conversion.
[0027] 2. This application applies the Mxene composite bimetallic material to the diaphragm coating of the lithium-sulfur battery. The material exhibits excellent rate capability, very good cycle stability and high specific capacity under high sulfur loading and low electrolyte conditions.
[0028] 3. This application adopts an in-situ growth method when compounding Mxene materials and bimetallic organic frameworks. This method can give full play to the high specific surface area characteristics of two-dimensional materials and avoid agglomeration effects. Specifically, the fibrous bimetallic organic framework material assembled on the Mxene material can synergistically prevent the aggregation of its own metal materials and the re-accumulation of the active area of the Mxene nanosheets during the lithium polysulfide conversion process.
[0029] 4. The Mxene composite bimetallic material prepared in this application can not only strongly adsorb polysulfides, but also accelerate the kinetic process of polysulfide redox, and suppress the shuttle effect and reduce the loss of active substances to the greatest extent. At the same time, when the prepared Mxene composite bimetallic material is used to construct a diaphragm coating, the lithium-sulfur battery shows excellent electrochemical performance, and the battery's rate performance and cycle stability are improved.
[0030] 5. The MXene composite bimetallic material prepared in the present application also has excellent chemical stability. After being immersed in the electrolyte for more than 10 days, there is still no obvious dissolution phenomenon and the crystal form is well maintained, that is, its framework structure has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0032] Figure 1 This is a schematic diagram of the preparation process of the Mxene composite bimetallic material of Example 1;
[0033] Figure 2 This is a scanning electron microscope image of the Mxene material obtained in Example 1;
[0034] Figure 3 This is a scanning electron microscope image of the Mxene composite bimetallic material obtained in Example 1;
[0035] Figure 4 This is a transmission electron microscope image of the Mxene composite bimetallic material obtained in Example 1;
[0036] Figure 5 Quantitative comparative analysis of the adsorption of lithium hexasulfide by the Mxene composite bimetallic material obtained in Example 1 and the nickel / manganese bimetallic organic framework;
[0037] Figure 6This is an analysis chart of the inductively coupled plasma emission spectrum data of the Mxene composite bimetallic material obtained in Example 2-12;
[0038] Figure 7 This is the nucleation curve of lithium sulfide deposition of the Mxene material obtained in Example 1 in a lithium-sulfur battery;
[0039] Figure 8 This is the nucleation curve of lithium sulfide deposition of the Mxene composite bimetallic material obtained in Example 1 in a lithium-sulfur battery;
[0040] Fig. 9 The assembled battery obtained in Example 13 was -1 Cyclic voltammetry curves at a scan rate of ;
[0041] Fig.10 The modified membrane material obtained in Example 13 is 1.8 mg cm -1 Long-term cycling performance at sulfur loading and current density 2C. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0043] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0044] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0045] In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.
[0046] The disclosure below provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the disclosure of the present application, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the various specific processes and material examples provided by the present application, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.
[0047] Example 1
[0048] A method for preparing a MXene composite bimetallic material comprises the following steps:
[0049] (1) Preparation of Mxene materials
[0050] Weigh 5g of Ti3AlC2 powder, mix it with 30ml of ethanol, put it into a ball mill, and grind it at 600rpm for 4 hours to obtain a uniform slurry; filter the slurry and place it in a vacuum oven at 60°C to dry for 12h to obtain a dry powder; take 180mg of dry powder, put it into a pressure bottle together with 3ml of HF and 60ml of deionized water, mix it and heat it to 180°C and keep it for 10 hours, then cool it naturally to room temperature; collect the product and wash it three times with N,N-dimethylformamide to obtain Mxene material.
[0051] (2) Modification of Mxene materials
[0052] The Mxene material obtained in step (1) was placed in 60 ml of a tetraethylammonium hydroxide solution having a mass concentration of 33%, stirred for 4 hours, and then centrifuged to obtain a modified Mxene material.
[0053] (3) Preparation of Mxene composite bimetallic materials
[0054] Weigh 10 mg of terephthalic acid and dissolve it in a mixed solution of 2 ml of N,N-dimethylformamide and 1 ml of acetonitrile to obtain a base solution;
[0055] Weigh 5 mg of the modified Mxene material obtained in step (2), dissolve it in a mixed solution of 1 ml of N,N-dimethylformamide and 1 ml of acetonitrile and stir for 1 hour to obtain a middle layer solution;
[0056] 12.63 mg of metal salt ligand powder is dissolved in a mixed solution of 1 ml of N,N-dimethylformamide and 2 ml of acetonitrile to obtain an upper layer liquid; wherein the metal ligand powder includes Ni(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O, and the molar ratio of Ni(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O is 4:1, that is, Ni(CH3COO)2·4H2O is 9.95 mg, and Mn(CH3COO)2·4H2O is 2.68 mg.
[0057] The bottom liquid, the middle liquid and the upper liquid are slowly poured into the reaction bottle in sequence and are always kept superimposed and in a layered state, that is, the bottom liquid is located at the bottom of the reaction bottle, the middle liquid is located in the middle of the reaction bottle, and the upper liquid is located at the top of the reaction bottle. The reaction bottle is then placed at 15°C for reaction for 24 hours to obtain a reactant; the reactant is alternately centrifuged and washed 2-5 times with N,N-dimethylformamide and chloroform and then dried to obtain an Mxene composite bimetallic material.
[0058] Performance test 1
[0059] The Mxene material and the Mxene composite bimetallic material obtained in Example 1 were characterized for various properties. The results are as follows: Figure 1-4 The specific results are as follows:
[0060] Figure 1 The reaction process of preparing the Mxene composite bimetallic material in this embodiment is shown. It can be seen from the figure that the inorganic metal ion ligand is in the upper layer, the modified Mxene material is in the middle layer, and the organic ligand is in the bottom layer. During the static process, due to the concentration gradient between the layers, the upper layer and the bottom layer will eventually meet in the middle layer and grow in situ on the modified Mxene material, thereby forming a whole stable system.
[0061] Figure 2 This is a SEM image of the Mxene material obtained in step (1) of this embodiment. It can be seen from the figure that the Mxene material obtained in this embodiment has a multilayer structure.
[0062] Figure 3 This is the SEM image of the Mxene composite bimetallic material obtained in step (3) of this embodiment. It can be seen from the figure that the bimetallic organic framework material in situ grown on the Mxene material is evenly distributed on the Mxene material, and the introduction of two-dimensional Ti3C2Tx is conducive to the uniform dispersion of the bimetallic, thereby exposing active sites to promote charge transfer on the catalyst.
[0063] Figure 4 This is a TEM image of the Mxene composite bimetallic material obtained in step (3) of this embodiment, which shows the distribution of the fibrous bimetallic organic framework on the Mxene material. It can be further seen from the figure that the Mxene composite bimetallic material has a porous structure and a large comparative area. The equilibrium valence state of Ni and Mn in the porous bimetallic organic framework and its coordination ability with LiPSs provide suitable adsorption capacity and higher catalytic activity, so that LiPSs can be efficiently captured and quickly converted. At the same time, the interwoven conductive network provides a catalytic conversion with rich active sites and a high specific surface area.
[0064] Figure 5 This is a quantitative comparative analysis of the adsorption of lithium hexasulfide by the Mxene composite bimetallic material and the nickel / manganese bimetallic organic framework obtained in step (3) of the embodiment. As can be seen from the figure, the adsorption capacity of the Mxene composite bimetallic material for polysulfide is significantly better than that of the nickel / manganese bimetallic organic framework, and the synergistic effect of the combination of the Mxene material and the nickel / manganese bimetallic organic framework significantly improves the adsorption performance of polysulfide. The nickel / manganese bimetallic organic framework adopts the nickel / manganese bimetallic organic framework conventionally used in the prior art.
[0065] Example 2-12
[0066] The difference between Example 2-12 and Example 1 is that the molar ratio of Ni(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O in step (3) is different and / or the temperature during the static reaction is different, wherein the molar ratio of Ni(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O in Example 2-12 is different and the specific temperature during the static reaction is shown in Table 1 below:
[0067] Table 1 Mn / Ni molar ratio and static reaction temperature in Examples 2-12
[0068] serial number Mn / Ni molar ratio Reaction temperature / ℃ Example 2 1:4 20 Example 3 1:4 10 Example 4 1:3 20 Example 5 1:3 15 Example 6 1:3 10 Example 7 1:2 20 Example 8 1:2 15 Example 9 1:2 10 Example 10 1:1 20 Embodiment 11 1:1 15 Example 12 1:1 10
[0069] The Mxene composite bimetallic materials obtained in the above examples 1-12 were subjected to inductively coupled plasma emission spectroscopy data analysis, and the analysis results were as follows: Figure 6 As shown in the figure, when the Mn / Ni reaction molar ratio is 1:4 and the temperature is 15°C (Example 1), the effective metal component is the highest, which can provide spatial confinement of polysulfides and abundant catalytic sites. It has long-term stability, ion shielding, high polysulfide adsorption capacity and multi-step catalytic conversion ability. In addition, the local electrons of the effective bimetallic give the cathode excellent electron / lithium ion transfer ability. The synergistic effect of the bimetallic can significantly promote the interfacial charge transfer kinetics, promote sulfur conversion kinetics and inhibit shuttling.
[0070] Embodiment 13
[0071] The Mxene composite bimetallic material obtained in Example 1 is applied to the separator of a lithium-sulfur battery and a lithium-sulfur battery is prepared, wherein the preparation method of the lithium-sulfur battery comprises the following steps:
[0072] (1) Preparation of modified membrane
[0073] The Mxene composite bimetallic material, conductive carbon black and polyvinylidene fluoride (PVDF) obtained in Example 1 were weighed according to weights of 200 mg, 250 mg and 50 mg respectively, mixed and ground for 10 min and placed in a sealed glass bottle, N-methylpyrrolidone (NMP) solvent was added dropwise to the glass bottle, and then strongly magnetically stirred for 10 h to form a uniform slurry, and the slurry was evenly coated on a polypropylene diaphragm (a diaphragm of model Celgard 2400 was used) with a scraper, and then dried naturally for 30 min and placed in a vacuum drying oven at 65 ° C for 12 h. Finally, the dried diaphragm was punched into a disc with a diameter of 16 mm using a mold to obtain a modified diaphragm for use.
[0074] (2) Preparation of sulfur cathode
[0075] Weigh 160 mg, 20 mg, and 20 mg of sublimed sulfur, acetylene black, and 5% LA 133 by weight respectively. After mixing, ball mill them for 30 min using a ball mill. Drop an appropriate amount of a mixed solvent of water and propanol, and then stir vigorously with a magnetic stirrer for 5 h to form a uniform slurry. Use a spatula to evenly coat the slurry on a carbon-aluminum foil current collector, and dry it overnight in an oven at 65 °C. Punch it into a disc with a diameter of 10 mm to obtain a sulfur cathode.
[0076] (3) Preparation of a lithium-sulfur battery
[0077] Place the metallic lithium anode, an organic ether-based electrolyte containing a lithium nitrate additive, the modified separator obtained in step (1), and the sulfur cathode obtained in step (2) in an argon atmosphere glove box with a water and oxygen content of less than 0.1 ppm to complete the assembly of a CR2032 coin cell, thereby obtaining a lithium-sulfur battery.
[0078] When assembling the battery, the modified side of the modified separator faces the sulfur cathode side. The electrolyte of the organic ether-based electrolyte containing a lithium nitrate additive is 1 M lithium bis(trifluoromethanesulfonyl)imide salt (LiTFSI), which is dissolved in a solution of 1,3-dioxolane (DOL) and dimethoxymethane (DME) (1:1 v / v), and also contains 0.1 M LiNiO3 additive.
[0079] Performance test two
[0080] Use the Land CT2001 battery test system to conduct various electrochemical performance tests on the modified separator and lithium-sulfur battery obtained in Example 13. The test results are as Figures 6 to 10 shown, and the specific results are as follows:
[0081] When scanning the lithium-sulfur battery assembled with the modified separator material prepared in step (1) of this example by cyclic voltammetry at a scan rate of 0.1 mV s -1 , it can be obtained that there are negligible current changes and potential hysteresis phenomena in the CV peaks of the lithium-sulfur battery assembled with the modified separator material. When the battery is scanned in the positive direction, there are two peaks at ~2.33 V and ~2.08 V. The first peak is related to the reduction of S8 to polysulfide (Li2S x , 4 < x ≤ 8), and the second peak corresponds to the subsequent reduction of Li2S4 to Li2S2 and Li2S. Subsequently, two peaks appear at 2.3 - 2.4 V during the reverse scan, which respectively correspond to the oxidation of Li2S2 / Li2S to long-chain Li2S x , and finally oxidized to S8. This indicates that the Mxene composite bimetallic material has good redox reaction kinetics.
[0082] Figure 7is the nucleation curve of lithium sulfide deposition of the Mxene material obtained in Example 1 in a lithium-sulfur battery, Figure 8 This is the nucleation curve of lithium sulfide deposition of Mxene composite bimetallic material in lithium-sulfur battery. Figure 7 and Figure 8 It can be seen that different catalysts have different effects on the kinetics of sulfur reduction reactions. According to Faraday's law, the deposition capacity of lithium sulfide after the addition of electrocatalysts was calculated. The deposition capacity of the Mxene composite bimetallic material was calculated to be 116..9mAh g-1, which is greater than the deposition capacity of the Mxene material, indicating that the addition of the Mxene composite bimetallic material not only effectively accelerates the conversion of polysulfides, but also contributes to the rapid deposition of lithium sulfide. According to the nucleation model, the uniqueness of the nucleation mode of lithium sulfide in the Mxene composite bimetallic material indicates that its nucleation is not affected by the crystal surface and is easier to nucleate and grow. In addition to the lithium sulfide deposition process, the dissolution rate is also particularly important. The rapid oxidation and dissolution of lithium sulfide during the charging process can avoid the accumulation of low-activity lithium sulfide and the blockage of the active sites of the electrocatalyst. It also shows the excellent bidirectional redox characteristics of the Mxene composite bimetallic material electrocatalyst.
[0083] Fig. 9 For three different assembled batteries at 50 mV s -1 Cyclic voltammetry curves at a scan rate of , wherein three different groups of assembled batteries include: 1. The assembled battery obtained in step (3) of this embodiment; 2. The assembled battery obtained by using Mxene material as the preparation of the modified diaphragm instead of the Mxene composite bimetallic material in this embodiment; 3. The assembled battery obtained by using an organic ether electrolyte without lithium nitrate additives instead of the organic ether electrolyte containing lithium nitrate additives in this embodiment. As can be seen from the figure, the assembled battery obtained by using the Mxene composite bimetallic material to prepare the modified diaphragm has a stronger current response than the assembled battery obtained by using the Mxene material to prepare the modified diaphragm. The assembled battery prepared using an organic ether electrolyte without lithium nitrate additives has no current response. This indicates that the current response is caused by the transformation of polysulfides, and also proves that the Mxene composite bimetallic has a strong current response to the electrolyte and has better redox kinetics.
[0084] Fig.10 The modified membrane material obtained in this example is 1.8 mg cm -1 The long-term cycle performance diagram of sulfur loading and current density 2C. It can be seen from the figure that it has good initial specific capacity, long cycle performance and capacity retention rate.
[0085] Examples 14-17
[0086] The difference between Examples 14-17 and the above-mentioned Example 1 is that the metal salt ligand powder in step (3) is different. The metal salt ligand powder used in Examples 14-17 is specifically shown in Table 2 below:
[0087] Table 2 Metal salt ligand powder used in Examples 13-16
[0088] serial number Powder A Powder B Embodiment 14 <![CDATA[Zn(CH3COO)2·2H2O]]> <![CDATA[Mn(CH3COO)2·4H2O]]> Embodiment 15 <![CDATA[Cu(CH3COO)2·H2O]]> <![CDATA[Mn(CH3COO)2·4H2O]]> Example 16 <![CDATA[Fe(CH3COO)3·4H2O]]> <![CDATA[Mn(CH3COO)2·4H2O]]> Embodiment 17 <![CDATA[Co(CH3COO)2·4H2O]]> <![CDATA[Mn(CH3COO)2·4H2O]]>
[0089] Performance Test Three
[0090] The Mxene composite bimetallic materials obtained in Examples 1 and 14-17 were subjected to comprehensive electrochemical performance testing according to the method in Example 13, and the test results are shown in Table 3 below:
[0091] Table 3 Electrochemical properties of Mxene composite bimetallic materials obtained in Examples 1, 14-17
[0092]
[0093] It can be seen from the test results in Table 3 that under the same conditions, the Mxene composite bimetallic material prepared by Ni and Mn bimetallic compound has the best comprehensive electrochemical performance.
[0094] Comparative Example 1
[0095] A method for preparing a MXene composite bimetallic material comprises the following steps:
[0096] (1) Preparation of Mxene materials
[0097] Weigh 5g of Ti3AlC2 powder, mix it with 30ml of ethanol, put it into a ball mill, and grind it at 600rpm for 4 hours to obtain a uniform slurry; filter the slurry and place it in a vacuum oven at 60°C to dry for 12h to obtain a dry powder; take 180mg of dry powder, put it into a pressure bottle together with 3ml of HF and 60ml of deionized water, mix it and heat it to 180°C and keep it for 10 hours, then cool it naturally to room temperature; collect the product and wash it three times with N,N-dimethylformamide to obtain Mxene material.
[0098] (2) Modification of Mxene materials
[0099] The Mxene material obtained in step (1) was placed in 60 ml of a tetraethylammonium hydroxide solution having a mass concentration of 33%, stirred for 4 hours, and then centrifuged to obtain a modified Mxene material.
[0100] (3) Preparation of Mxene composite bimetallic materials
[0101] Weigh 10 mg of terephthalic acid and dissolve it in a mixed solution of 2 ml of N,N-dimethylformamide and 1 ml of acetonitrile to obtain a base solution;
[0102] Weigh 5 mg of the modified Mxene material obtained in step (2), dissolve it in a mixed solution of 1 ml of N,N-dimethylformamide and 1 ml of acetonitrile and stir for 1 hour to obtain a middle layer solution;
[0103] Dissolve Ni(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O metal salt ligand powders in a molar ratio of 4:1 in a mixed solution of 1 ml of N,N-dimethylformamide and 2 ml of acetonitrile to obtain an upper layer liquid;
[0104] The bottom liquid, the middle liquid and the upper liquid are poured into a reaction bottle in turn and stirred at 15° C. for 24 hours to obtain a reactant; the reactant is alternately centrifuged and washed 2-5 times with N,N-dimethylformamide and chloroform and then dried to obtain a Mxene composite bimetallic material.
[0105] The difference between this comparative example and the above-mentioned Example 1 is that the nickel-manganese bimetallic organic framework is directly mixed with the modified Mxene material. In order to verify the performance stability of the Mxene composite bimetallic material obtained in this comparative example 1, the Mxene composite bimetallic materials obtained in Example 1 and this comparative example 1 are respectively placed in an organic ether electrolyte containing a lithium nitrate additive and allowed to soak. After soaking for 3 days, the Mxene composite bimetallic material obtained in comparative example 1 partially dissolved, indicating that the structure of the Mxene composite bimetallic material obtained in comparative example 1 has begun to collapse, and it can be seen that its electrolyte resistance and chemical stability are poor. However, the Mxene composite bimetallic material obtained in Example 1 still did not dissolve after soaking for 10 days. It shows that the Mxene composite bimetallic material prepared by in-situ interfacial polymerization has better electrolyte resistance and chemical stability.
[0106] Comparative Example 2
[0107] The difference between this comparative example 2 and the above-mentioned embodiment 1 is that the modified Mxene material in embodiment 1 is replaced by graphene. The yield of the product obtained in embodiment 1 is 93%, and the yield of the product obtained in comparative example 2 is 77%. It can be seen that under the same conditions, the yield of using Mxene is greater than the yield of using graphene, and the cost of using graphene ligands is about 2.4 times that of Mxene ligands, which is not conducive to the systematic application of subsequent lithium-sulfur batteries.
[0108] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0109] The above is a detailed introduction to the preparation method of a Mxene composite bimetallic material provided in the embodiment of the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a Mxene composite bimetallic material, characterized in that: The steps include: (1) Preparation of Mxene materials Mix Ti3AlC2 powder with ethanol and grind it in a ball mill to obtain a uniform slurry; dry the slurry to obtain dry powder; heat the dry powder, HF and deionized water in a pressure bottle to 150-200°C and keep it for 4-10 hours, then cool it naturally to room temperature; then wash it with N,N-dimethylformamide to obtain Mxene material; (2) Modification of Mxene materials The Mxene material obtained in step (1) is placed in a tetraethylammonium hydroxide solution, stirred for 3-5 hours, and then centrifuged to obtain a modified Mxene material; (3) Preparation of Mxene composite bimetallic materials Dissolving terephthalic acid in a mixed solution of N,N-dimethylformamide and acetonitrile to obtain a base solution; Dissolving the modified Mxene material obtained in step (2) in a mixed solution of N,N-dimethylformamide and acetonitrile and stirring evenly to obtain a middle layer liquid; Dissolving the metal salt ligand powder in a mixed solution of N,N-dimethylformamide and acetonitrile to obtain an upper layer liquid; The bottom liquid, the middle liquid and the upper liquid are sequentially poured into the reaction bottle and the bottom liquid, the middle liquid and the upper liquid are always kept sequentially stacked and in a layered state, and then the reaction bottle is placed at 15-25° C. for 10-24 hours to react to obtain a reactant; The reactants are alternately centrifuged and washed 2-5 times with N,N-dimethylformamide and chloroform and then dried to obtain the Mxene composite bimetallic material.
2. The method for preparing the Mxene composite bimetallic material according to claim 1, characterized in that: The mixing ratio of the Ti3AlC2 powder and the ethanol in the step (1) is 1g: (4-6)ml.
3. The method for preparing the Mxene composite bimetallic material according to claim 1, characterized in that: In the step (1), the ball mill has a rotation speed of 600 rpm and a grinding time of 3-5 h.
4. The method for preparing the Mxene composite bimetallic material according to claim 1, characterized in that: The addition ratio of the dry powder, HF and deionized water in step (1) is (150-200) mg: 3 ml: 60 ml.
5. The method for preparing the Mxene composite bimetallic material according to claim 1, characterized in that: The concentration of the tetraethylammonium hydroxide solution in step (2) is (30-35) wt%.
6. The method for preparing the Mxene composite bimetallic material according to claim 1, characterized in that: The addition ratio of terephthalic acid in the base liquid to the modified Mxene material in the middle layer liquid is 2:
1.
7. The method for preparing the Mxene composite bimetallic material according to claim 1, characterized in that: The metal salt ligand powder in step (3) includes powder A and powder B, wherein powder A is any one of Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O, Zn(CH3COO)2·2H2O, Fe(CH3COO)3·4H2O, and Cu(CH3COO)2·H2O, and powder B is Mn(CH3COO)2·4H2O.
8. The method for preparing the Mxene composite bimetallic material according to claim 1, characterized in that: The molar ratio of the powder A to the powder B is (1-4):
1.
9. A Mxene composite bimetallic material, characterized in that: The method is as described in any one of claims 1 to 8.
10. A lithium-sulfur battery comprising a modified separator, characterized in that: The modified diaphragm is coated with a Mxene composite bimetallic material prepared by the preparation method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of functional barrier layer of self-supporting lithium-sulfur battery
CN111370629A
Preparation method of Zn-based dual-MOF modified diaphragm for lithium-sulfur battery as well as product and application of Zn-based dual-MOF modified diaphragm
CN115810865A
Layered compound / Mxene heterojunction functional material for lithium-sulfur battery
CN115842216A